Optimization of Elementary School Learning Processes through a Multi-Platform E-Learning System - Akbar, Wahyu; Puji Sejati, Rr. Hajar (Kirana Publisher (KNPub), 2025)
The transformation of digital learning requires an integrated platform that can effectively support academic processes at the elementary school level. This study aims to develop an integrated multi platform e learning system for SD Negeri Tengah 08 Jakarta to optimize the efficiency of academic management and the flexibility of learning access. The system was built using a RESTful API architecture with Golang as the backend, PostgreSQL as the database, React.js for the web interfaces (Teachers and Administrators), and Flutter for the mobile application (Students). Based on the system development method and Black Box Testing, the results show that the integration successfully enables real time data synchronization without technical issues. All functional features, including NISN based authentication, automated scheduling, material distribution, and interactive quiz evaluation, were validated successfully. This implementation significantly establishes a responsive digital learning ecosystem, streamlines teachers’ administrative workload, and enhances student engagement in flexible self directed learning, while strengthening the consistency of a structured, adaptive, and sustainable online learning process for all school stakeholders.